Laparoscopic Peritoneal Lavage. Issue 1 (January 2015) - Cirocchi, Roberto; Trastulli, Stefano; Vettoretto, Nereo; Milani, Diego; Cavaliere, Davide; Renzi, Claudio; Adamenko, Olga; Desiderio, Jacopo; Burattini, Maria Federica; Parisi, Amilcare; Arezzo, Alberto; Fingerhut, Abe; et al.
<x xml:space="preserve">Abstract</x> Abstract To this day, the treatment of generalized peritonitis secondary to diverticular perforation is still controversial. Recently, in patients with acute sigmoid diverticulitis, laparoscopic lavage and drainage has gained a wide interest as an alternative to resection. Based on this backdrop, we decided to perform a systematic review of the literature to evaluate the safety, feasibility, and efficacy of peritoneal lavage in perforated diverticular disease. A bibliographic search was performed in PubMed for case series and comparative studies published between January 1992 and February 2014 describing laparoscopic peritoneal lavage in patients with perforated diverticulitis. A total of 19 articles consisting of 10 cohort studies, 8 case series, and 1 controlled clinical trial met the inclusion criteria and were reviewed. In total these studies analyzed data from 871 patients. The mean follow-up time ranged from 1.5 to 96 months when reported. In 11 studies, the success rate of laparoscopic peritoneal lavage, defined as patients alive without surgical treatment for a recurrent episode of diverticulitis, was 24.3%. In patients with Hinchey stage III diverticulitis, the incidence of laparotomy conversion was 1%, whereas in patients with stage IV it was 45%. The 30-day postoperative mortality rate was 2.9%. The 30-day postoperative reintervention rate was 4.9%, whereas 2% of patients required a percutaneous drainage. Readmission rate after the first hospitalization for recurrent diverticulitis was 6%. Most patients who were readmitted (69%) required redo surgery. A 2-stage laparoscopic intervention was performed in 18.3% of patients. Laparoscopic peritoneal lavage should be considered an effective and safe option for the treatment of patients with sigmoid diverticulitis with Hinchey stage III peritonitis; it can also be consider as a "bridge" surgical step combined with a delayed and elective laparoscopic sigmoidectomy in order to avoid a Hartmann procedure. This minimally invasive staged approach should be considered for patients without systemic toxicity and in centers experienced in minimally invasive surgery techniques. Further evidence is needed, and the ongoing RCTs will better define the role of the laparoscopic peritoneal lavage/drainage in the treatment of patients with complicated diverticulitis.